PENERAPAN NORMA DAN ASAS-ASAS HUKUM ADAT DALAM PRAKTIK PERADILAN PERDATA - Mr. Sulastriyono; Sandra Dini Febri Aristya (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2012)
This research was descriptive research. Secondary and primary data were analysed qualitatively. The result of the research shows that mostly, the application of adat law norm and principles appear in the domain of private, contract, marital, and inheritance law. The adat law norms which are frequently used as judge considerations are the right of spouse on the matrimonial property, the guardian of a child under his mother, and the status of ex-wife as the heir of her former husband. We also identify a number of adat law principles, which include the clear (terang), cash (tunai), real (konkret) and familiarity (kekeluargaan). Application of adat law is necessary owing to the normative legislative obligation. In practice, judges need to ensure that adat law norms are consistent with the applicable civil procedure. Penelitian ini bersifat deskriptif, yaitu melukiskan fakta obyek penelitian. Data primer dan sekunder dianalisis secara kualitatif. Hasil penelitian menunjukkan bahwa norma hukum adat yang dijadikan dasar pertimbangan putusan hakim adalah istri berhak atas harta bersama, anak kecil diasuh ibu yang bercerai, dan istri adalah ahli waris mendiang suaminya. Asas hukum adat yang mendasari putusan hakim mencakup asas terang, tunai, konkrit dan kekeluargaan. Alasan hakim menerapkan norma dan asas hukum adat dikarenakan kewajiban normatif dari undang-undang dan dalam upaya membentuk yurisprudensi. Namun, praktiknya tidak mudah sehingga hakim harus melakukan harmonisasi ke dalam hukum acara positif.